Effects of organic farming adoption on farmer’s subjective well-being: evidence from Xiangxi Prefecture, China - Pingan Xiang; Chi Wen; Zhifen Lin; Maosen Xia (International Journal of Agricultural Sustainability)
Examining the relationship between organic farming adoption (OFA) and subjective well-being (SW) is crucial for understanding farmers' adoption behavior regarding organic farming and the factors facilitating its dissemination. This paper utilizes a sample of 450 farmers from four counties in the Xiangxi Tujia and Miao Autonomous Prefecture of Hunan Province, China, to compare the SW of conventional and organic farmers. Based on the Millennium Ecosystem Assessment well-being framework, using the ordered probit model, we analyzed the mechanisms of OFA on the SW of organic farmers, including the subgroups of conversion farmers and certified farmers. The results indicated that organic farmers reported higher SW than conventional farmers. The positive effect of OFA on SW of organic farmers was not present in the conversion period but was statistically significant in the certification period. Farm profitability, health, environmental quality, and food safety were mediators of OFA on SW, although the mediating effects of health and food safety didn't apply to conversion farmers. Findings from this study provide information on how OFA affects SW, which can be useful for governments to develop supportive policies to attract conventional farmers and stabilize organic farmers to adopt organic farming.